Proteomics Analysis of Three Different Strains of Mycobacterium tuberculosis under In vitro Hypoxia and Evaluation of Hypoxia Associated Antigen’s Specific Memory T Cells in Healthy Household Contacts - Devasundaram, Santhi; Gopalan, Akilandeswari; Das, Sulochana D.; Raja, Alamelu (Frontiers in Microbiology, 2016)
In vitro mimicking conditions are thought to reflect the environment experienced by M. tuberculosis inside the host granuloma. The majority of the in vitro dormancy experimental models used laboratory adapted strain H37Rv or Erdman strain over the prevalent clinical strains involved during disease outbreaks. Thus, we included the most prevalent clinical strains (S7 and S10) of M. tuberculosis from south India in addition to H37Rv for our in vitro oxygen depletion (hypoxia) experimental model. Cytosolic proteins were prepared from the hypoxic cultures, resolved by two-dimensional electrophoresis (2-DE) and protein spots were characterized by mass spectrometry. Totally 49 spots were characterized as over-expressed or newly appeared between the 3 strains. Two antigens (ESAT-6, Lpd) out of the 49 characterized spots were readily available in recombinant form in our lab. Hence, these 2 genes were overexpressed, purified and used for in vitro stimulation of whole blood collected from healthy household contacts (HHC) and active pulmonary tuberculosis patients (PTB). Multicolour flow cytometry analysis showed high levels of antigen specific CD4+ central memory T cells in circulation of HHC when compared to PTB (p<0.005 for ESAT-6 and p<0.0005 for Lpd). This shows proteins that are predicted to be upregulated during in vitro hypoxia in most prevalent clinical strains would bring the possible potential immunogens. In vitro hypoxia experiments with most prevalent clinical strains would also bring the probable true representative antigens that involved during adaption mechanism.